2011
DOI: 10.1105/tpc.111.092684
|View full text |Cite
|
Sign up to set email alerts
|

MDP25, A Novel Calcium Regulatory Protein, Mediates Hypocotyl Cell Elongation by Destabilizing Cortical Microtubules inArabidopsis     

Abstract: The regulation of hypocotyl elongation is important for plant growth. Microtubules play a crucial role during hypocotyl cell elongation. However, the molecular mechanism underlying this process is not well understood. In this study, we describe a novel Arabidopsis thaliana microtubule-destabilizing protein 25 (MDP25) as a negative regulator of hypocotyl cell elongation. We found that MDP25 directly bound to and destabilized microtubules to enhance microtubule depolymerization in vitro. The seedlings of mdp25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(169 citation statements)
references
References 47 publications
3
164
1
1
Order By: Relevance
“…Many microtubule regulatory proteins, such as SPR1 and MDP25, are involved in regulating hypocotyl cell elongation by altering the stability and organization of cortical microtubules (Nakajima et al, 2004(Nakajima et al, , 2006Li et al, 2011a). This study showed that the stability of cortical microtubules is decreased in hypocotyl epidermal cells following treatment with BL, which likely explains the underlying mechanism regarding cortical microtubule reorientation in response to BR.…”
Section: The Involvement Of Microtubule Regulatory Proteins In Br-regmentioning
confidence: 64%
See 3 more Smart Citations
“…Many microtubule regulatory proteins, such as SPR1 and MDP25, are involved in regulating hypocotyl cell elongation by altering the stability and organization of cortical microtubules (Nakajima et al, 2004(Nakajima et al, , 2006Li et al, 2011a). This study showed that the stability of cortical microtubules is decreased in hypocotyl epidermal cells following treatment with BL, which likely explains the underlying mechanism regarding cortical microtubule reorientation in response to BR.…”
Section: The Involvement Of Microtubule Regulatory Proteins In Br-regmentioning
confidence: 64%
“…BZR1 functions in rapidly growing etiolated hypocotyl cells but not in cells that are in a stationary growth phase (Wang et al, 2002). Transverse patterns of cortical microtubules, which are associated with cells in a rapid growth phase, are detected in rapidly elongating etiolated hypocotyl epidermal cells (Le et al, 2005;Li et al, 2011a;Crowell et al, 2011). The orientation of cortical microtubules is interrelated with hypocotyl cell elongation, which has been tested using microtubule-disrupting drugs and the mutant and transgenic lines of microtubule regulatory proteins (Le et al, 2005;Paredez et al, 2006;Somerville, 2006;Buschmann and Lloyd, 2008).…”
Section: The Reorientation Of Cortical Microtubules Is Necessary For mentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that a range of mutants altered in MT stability exhibit defects in cell growth (Ishida et al, 2007a;Perrin et al, 2007;Wang et al, 2007Wang et al, , 2012Yao et al, 2008;Li et al, 2011a) suggests that proper MT dynamics and stability may be key to proper cell expansion. Given our data showing that the cortical MT arrays in spr1-6 eb1b-2 expanding root and etiolated hypocotyl cells have relatively normal organization (Figure 4), it seems unlikely that the severe anisotropic expansion defects of these cells is due to the orientation and ordering of cortical MTs and, by extension, oriented cellulose deposition.…”
Section: Discussionmentioning
confidence: 99%